Prevalence of Drug Prescriptions and Potential Safety in Patients with Cirrhosis: A Retrospective Real-World Study - Weersink, Rianne A. (Drug Saf, 2018)
INTRODUCTION: Patients with cirrhosis are at risk for adverse drug reactions (ADRs) due to altered pharmacokinetics and pharmacodynamics. We aimed to determine the prevalence of drug prescriptions and the potential safety of these prescriptions in a real-world cohort of patients with cirrhosis. METHODS: This was a retrospective cohort study based on linked real-world data from the Out-patient Pharmacy Database and the Hospitalisation Database of the PHARMO Database Network. Patients with a diagnosis of cirrhosis between January 1998 and December 2015 were included. Follow-up ended when the patient underwent a liver transplant, died, transferred out of the database, or on 31 December 2015. Prescription data were derived from a community pharmacy database and were compared with our previously developed safety recommendations for 209 drugs. RESULTS: In total, 5618 patients were included and followed for a median of 3 years (interquartile range [IQR] 1–7). In the first year after the diagnosis, patients used a median of nine drugs (IQR 5–14), with proton pump inhibitors (prevalence 53.9%), aldosterone antagonists (43.6%), and sulfonamide diuretics (41.3%) being the most commonly used drug groups. Almost half (48.3%) of 102,927 prescriptions consisted of drugs with a safety recommendation. The prevalence of potentially unsafe drug use was 60.0% during the total follow-up. Three nonsteroidal anti-inflammatory drugs (NSAIDs) were among the five most commonly used potentially unsafe drugs. CONCLUSIONS: Patients with cirrhosis use a large number of drugs. Almost two-thirds of patients in our cohort used potentially unsafe drugs. To prevent ADRs in these frail patients, personalised pharmacotherapy is necessary. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40264-018-0744-1) contains supplementary material, which is available to authorized users.